Attenuation of neutrophil adhesion and formation of neutrophil extracellular traps by pooled human immune globulins - Rao, Vidhya R.; Iqbal, Sana; Young, Bradford A.; Mun, Christine; Jain, Sandeep; Kaja, Simon (Frontiers in Pharmacology, 2024)
Introduction: This study investigated the efficacy of pooled human immune globulins (Flebogamma ® DIF) to combat the formation of neutrophil extracellular traps (NETs) and NETosis, along with neutrophil adhesion to corneal epithelial cells in response to dry eye disease relevant stimuli.Methods: Human neutrophils were isolated by bead-based immunomagnetic depletion of non-target cells from human whole blood. NETosis was induced using phorbol 12-myristate 13-acetate (PMA) or anti-citrullinated histone 4 R3 antibody (H4R3 ACPA). Extracellular DNA was used as a surrogate biomarker of NETosis, and it was quantified using a 96-well, plate reader-based fluorescent assay and by confocal microscopy in 8-well chambers using the DNA dye, SYTOX TM Green. Neutrophils were labeled with calcein-AM and adhesion to human corneal epithelial cells was measured. The efficacy of a dose-range of pooled human immune globulin (Flebogamma® DIF, 0.01% -5%) was tested in all assays.Results: Pooled human immune globulins (Flebogamma® DIF) dose-dependently inhibited both PMA and H4R3 ACPA induced NETosis, with concentrations ³ 2.5% fully preventing release of extracellular DNA over a 2 to 16 hour time period. Similarly, Flebogamma® 5% DIF prevented NETosis against PMA (20 nM) and a dose range (0.1 -10 µg/mL) of H4R3 ACPA. Both PMA and H4R3 ACPA increased adhesion of neutrophils to corneal epithelial cells by 20% and 5%, respectively. Flebogamma® DIF treatment resulted in a dose-dependent reduction of neutrophil adhesion, with Flebogamma® 5% DIF reducing adhesion to baseline levels.Discussion: These findings show the dose-dependent efficacy of pooled human immune globulins, specifically Flebogamma ® DIF against experimentally and pathologically induced NETosis and neutrophil adhesion to corneal epithelial cells, in vitro. The results from this study support the continued clinical development of Flebogamma ® 5% DIF as a novel and efficacious treatment for the signs and symptoms of dry eye disease.